Interference of the weight and boundary contour for algebraic polynomials in the weighted Lebesgue spaces. I - Abdullayev, F. G.; Özkartepe, N. P. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We study the order of the height of the modulus of arbitrary algebraic polynomials with respect to the weighted Lebesgue space, where the contour and the weight functions have some singularities.